ANALYSIS OF THE APPLICATION OF ONLINE TICKET BOOKING APPLICATION ACCESS BY KAI - Ririn Agus Triani; Femmy Sofie Schouten (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
This study aims to analyze the impact of the implementation of online ticket booking applications on the number of train passengers based on ticket sales data. The development of technology has brought significant changes in the transportation industry, including trains, with the introduction of online ticket booking applications. The analysis method used is a non-parametric statistical test to measure the relationship between the application and the number of passengers. Train ticket sales data for several years before and after the implementation of the application were used in the analysis. The results of the analysis showed a positive relationship between the implementation of online ticket booking applications and an increase in the number of train passengers. The findings support the view that the ease of access and convenience in booking tickets through the app has encouraged more people to use rail services. Although the results of this study indicate the positive impact of implementing online ticket booking applications, there are several other factors that can affect the number of passengers, such as economic factors, promotions, and additional services offered by train operators. Therefore, this study has limitations in considering all these factors. Based on these findings, it is recommended that train operators continue to develop and improve online ticket booking applications as part of their marketing and customer service strategies. This research contributes to understanding how technology can shape consumer behavior in the transportation industry and the extent of its impact on train passenger numbers.